Kecerdasan Emosional terhadap Kecanduan Bermain Game Online pada Remaja - Siregar, Monaria Jennifer Mapella; Alfita, Laili (Universitas Medan Area, 2025)
The study is entitled Emotional Intelligence against online gaming addiction in adolescents, where the study aims to look at the relationship between emotional intelligence and online gambling addiction among adolescents. The method used in this research uses a literature review, descriptive of the research article. The method in this study uses Systematic Literature Review (SLR) with PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) which is done in a systematic or phased manner. Based on an analysis of several journals, the researchers found a significant difference between emotional intelligence and online gaming addiction.